Siah Bisheh powerhouse cavern design modification using observational method and back analysis - Sharifzadeh, Mostafa; Masoudi, R.; Ghorbani, M. (2017)
© 2017 Taylor & Francis Group, London, UK. The Siah Bisheh pumped storage powerhouse cavern with complex geometry, changeable geological formations and diverse geotechnical properties of rocks, is under construction on the Chalus River 125 km north of Tehran, Iran. The powerhouse cavern was located near the downstream (d/s) dam reservoir and its crown was more than 30 meters lower than the downstream (d/s) dam maximum lake level. After impounding of the d/s dam, the powerhouse region would be located under saturated conditions. Therefore long term stability assessment of the powerhouse cavern under saturated conditions was unavoidable. In this study displacement based direct back analysis using variable staggered grid optimization algorithm was applied and calibrated geomechanical properties of rocks, stress ratio and joints parameters were identified. The time dependent behavior of rock was tested at the laboratory and the creep test results were considered in the practical design. Numerical modeling results were in good agreement with measured displacements of extensometers which confirmed the numerical modeling accuracy and back analysis results. Then ordinary analysis of the powerhouse cavern under natural conditions using back analysis results were carried out. Results of the analysis showed that the powerhouse cavern was stable under natural conditions and existing support system had suitable efficiency and could effectively control displacements. Finally, the powerhouse cavern long term stability under saturated conditions was analyzed. Results of analysis showed that after d/s dam impounding, pore water pressure and uplift pressure in discontinuities around the powerhouse cavern would arise so the powerhouse cavern tended to have local failure around the region 2nd and 3rd instrumentation arrays in the middle of the powerhouse cavern. To obtain powerhouse long term stability, it was recommended to construct a cutoff curtain grouting around powerhouse cavern.